2004
DOI: 10.1097/01.sla.0000141193.08524.e7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of a Randomized Controlled Trial of Suture Versus Mesh Repair of Incisional Hernia

Abstract: Objective: The objective of this study was to determine the best treatment of incisional hernia, taking into account recurrence, complications, discomfort, cosmetic result, and patient satisfaction. Background: Long-term results of incisional hernia repair are lacking. Retrospective studies and the midterm results of this study indicate that mesh repair is superior to suture repair. However, many surgeons are still performing suture repair. Methods: Between 1992 and 1998, a multicenter trial was performed, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
824
1
39

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,418 publications
(882 citation statements)
references
References 25 publications
18
824
1
39
Order By: Relevance
“…Incisional hernias are a major surgical complication occurring in at least 10-20% of all abdominal operations and need to be repaired in about one third of these patients. 6,17 Large trials have shown that hernia repair should be performed by mesh placement and no longer by primary resuturing of the hernia because of unacceptably high recurrence rates. 7,19 Mesh repair, however, is not free from complications, with significant factors being technical failure such as insufficient fixation of the mesh to the abdominal wall and complications which are a result of the mesh biomaterial itself.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Incisional hernias are a major surgical complication occurring in at least 10-20% of all abdominal operations and need to be repaired in about one third of these patients. 6,17 Large trials have shown that hernia repair should be performed by mesh placement and no longer by primary resuturing of the hernia because of unacceptably high recurrence rates. 7,19 Mesh repair, however, is not free from complications, with significant factors being technical failure such as insufficient fixation of the mesh to the abdominal wall and complications which are a result of the mesh biomaterial itself.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…16,22 The best method to repair these hernias is to implant a synthetic mesh that bridges the abdominal wall defect in a tension-free manner. [6][7][8]20 Such meshes are implanted in an open procedure or, with increasing frequency, laparoscopically. Despite important clinical successes, it is obvious that the ''ideal'' mesh is still not available.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce recurrence rates, synthetic meshes are employed, and their introduction was a milestone in hernia repair [3]. The ideal mesh should have no adhesion potential, excellent tissue integration, minimal shrinkage, and should be easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…From earlier studies it is known that the rate of incisional hernia increases during longer follow‐up18. In a comparison of suture repair with mesh repair of incisional hernia, delayed incisional hernia recurrence was shown after 10 years of follow‐up19. Experimental evidence, however, is supportive of the small‐bites technique.…”
Section: Discussionmentioning
confidence: 99%